2020
DOI: 10.1128/jvi.00841-20
|View full text |Cite
|
Sign up to set email alerts
|

ORF4 of the Temperate Archaeal Virus SNJ1 Governs the Lysis-Lysogeny Switch and Superinfection Immunity

Abstract: Recent environmental and metagenomic studies have considerably increased the repertoire of archaeal viruses and suggested that they play important roles in nutrient cycling in the biosphere. However, very little is known about how they regulate their life cycles and interact with their hosts. Here, we report that the life cycle of the temperate haloarchaeal virus SNJ1 is controlled by the product ORF4, a small protein belonging to the antitoxin MazE superfamily. We show that ORF4 controls the lysis-lysogeny sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…We assumed that if priority effects are driving persistence of a single version of pBI143, the first version that enters the infant gut environment should be maintained over time. Indeed, many phage populations are influenced by priority effects where the presence of one phage provides a competitive advantage to the host 88 or host immunity to infection with similar phages [89][90][91] . In our data, we found no instances where pBI143 acquired from the mother was fully replaced in the infant during and up to the first year of life (Supplementary Fig.…”
Section: Bacteroidales Speciesmentioning
confidence: 99%
“…We assumed that if priority effects are driving persistence of a single version of pBI143, the first version that enters the infant gut environment should be maintained over time. Indeed, many phage populations are influenced by priority effects where the presence of one phage provides a competitive advantage to the host 88 or host immunity to infection with similar phages [89][90][91] . In our data, we found no instances where pBI143 acquired from the mother was fully replaced in the infant during and up to the first year of life (Supplementary Fig.…”
Section: Bacteroidales Speciesmentioning
confidence: 99%
“…The Saline Natrinema sp. J7‐1 virus 1-encoded ORF4 is a transcriptional regulator belonging to the MazE superfamily and controls the lysis–lysogeny switch [3]. The virus is triggered to undergo the lytic life cycle upon treatment with the DNA-damaging agent mitomycin C. Homologues of Saline Natrinema sp.…”
Section: Replicationmentioning
confidence: 99%
“…2). Simuloviruses share 17-21 homologous ORFs including replication, regulation and virion structure-related genes; these gene modules are generally collinear among simuloviruses [3].…”
mentioning
confidence: 99%
“…In particular, we observed that 10 genomes infecting Methanobrevibacter_A smithii or M. olleyae encoded proteins belonging to the antitoxin MazE superfamily. The toxin-antitoxin system on a temperate virus acts as an addiction system, preventing the host from curing itself from the provirus 31 . Accordingly, the presence of the antitoxin MazE protein on the HGAVD archaeal viruses might highlight an arms race between the gut archaea and their viruses.…”
Section: Archaeal Virus Genomes Encode An Extensive Functional Repert...mentioning
confidence: 99%